Mangrove litter productivity after community forest implementation in Busung Village, Bintan Regency - Billa, Nur Salsa; Azizah, Diana; Susiana, Susiana (Sangia Research Media and Publishing, 2025)
Mangrove ecosystems play a crucial role both ecologically and economically. However, in Bintan Regency, their area has significantly declined due to development activities. This research aims to determine the productivity of the mangrove ecosystem in Busung Village, Bintan Regency, following the implementation of HKm. The study was conducted from April to May 2025 using a purposive sampling method with three observation stations, each consisting of three plots. Observations were made on litter production, decomposition, and mangrove crabs (Scylla sp.) parameters. Litter samples were collected using three 1×1 meter litter traps per plot, while decomposition was measured using litter bags, and mangrove crab samples were collected using foldable traps. Data correlation analysis between parameters was performed using Pearson correlation heatmaps and Principal Component Analysis (PCA). The results show that litter production in the Busung Village mangrove ecosystem was dominated by leaf components (19.51 g dry weight/m2 /10 days), with an average total production of 84.74 g dry weight/m2/10 days. Correlation analysis across the three stations indicated that mangrove crabs play a role in regulating mangrove litter productivity through their fragmentation/shredding activities, with varying influences depending on the level of human activity and environmental conditions. In areas with minimal activity (Station 1), an increase in crab density and weight significantly reduced the amount of litter. In fishing areas (Station 2), a healthy nutrient cycle was observed with positive correlations between parameters, while crabs controlled litter stock through consumption and fragmentation. In aquaculture areas (Station 3), the productive environment supported crab growth, although litter availability had less direct impact on the crabs.